PENGARUH PEMBELAJARAN NILAI-NILAI TOLERANSI UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA SMP - Nuswantari, Nuswantari (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2018)
The purpose of this research is, to know the influence of the tolerance values of teaching influence in improving social skill of junior high school’s students. Subject choice is done based on the score of social skill term to 143 students. As the subject of research is student who has < 111, and it is found 28 subject matters, and then from 28 subject concerned, it is divided into two groups, those are experiment’s group and controlled one, in random by considering equality if the subject between controlled and experiments groups. The result of data analysis of controlled and experiments groups with the t-test (sample paired t-test) it is known 2,490 with significant 0,027, it is mean there are differences of score improvement in social skill between controlled and experiences groups. It can be said that the instruction of effective tolerance values will result no difference, therefore it can be said that the effectivity of treatment will be fixed. The conclusion which will be found from this research is the teaching values of effective tolerance can be improving social skill of students.Keywords: social skill, tolerance, values